Pengaruh latihan lompat tangga terhadap kemampuan smash open bola voli pada club Amanuban Timur - Tlonaen, Aman Agung; M. Boleng, Lukas; J. H. Louk, Michael (Jurnal Ilmu Pendidikan Jasmani Kesehatan Dan Olahraga, 2024)
Thesis by Aman Agung Tlonaen, 1801150043, entitled: "The Effect of Stair Jumping Training on Volleyball Open Smash Ability in Amanuban Timur Club Volleyball Athletes". The author is supervised by Mr. Dr. Lukas M. Boleng, M.Kes and Mr. Michael Johannes H. Louk, S.Pd., M. The problem examined in this study was the open smash ability of the Amanuban Timur volleyball club. The purpose of this study was to determine how much influence ladder jumping training has on the ability to smash open volleyball in Amanuban Timur club volleyball athletes. Based on the results of research data obtained from the analysis: the average score of smash open players before being given treatment is 17,500 then the average score of smash open players after being given treatment is 25,375. Furthermore, the standard deviation or standard deviation was 3.36 smash open scores before treatment and 4.74 smash open scores after treatment. The amount of tcalculate = 9.364 > ttable = 2.13 with a significance of 5%, the p value obtained is 0.001 < 0.05. After calculating the percentage of exercise influence, the results obtained are 45%. So it can be concluded that the training given has an influence because of the increase in the ability to smash open volleyball athletes of the Amanuban Timur club.